Implementation of Natural Disaster Mitigation Learning Tsunami Material in Group B Kindergarten Harapan Jaya Tira, Sampolawa District, South Buton Regency - Yanti Indriani; Asma Kurniati; Siti Misra Susanti (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
Learning about natural disaster mitigation for children can develop children's preparedness in facing disasters. Natural disaster mitigation learning provides material about pre-disaster, during a disaster and post-disaster. In this research, researchers focus on learning about tsunami natural disaster mitigation. This research aims to find out how the tsunami natural disaster mitigation learning was carried out by Group B teachers at Harapan Jaya Tira Kindergarten, Sampolawa District, South Buton Regency. This research method uses descriptive qualitative methods with data collection techniques using observation, interviews and documentation methods. The first data analysis step is data reduction, the second is presentation of research data grouped based on theme findings and the last is the conclusion. The findings of this research show that teachers in Group B at Harapan Jaya Tira Kindergarten, Sampolawa District, South Buton Regency: 1) learning about natural disaster mitigation is included in the theme of the universe and the sub-theme of natural disasters, 2) conveys pre-disaster information, 3) conveys information during disasters and simulations during disasters, 4) conveying post-disaster information and post-disaster simulations, 5) applying learning methods for mitigating tsunami natural disasters using simulation methods and storytelling methods, 6) using learning media for mitigating tsunami natural disasters using image media.